Molecular Events Involved in Influenza A Virus-Induced Cell Death - Gui, Rui; Chen, Quanjiao (Frontiers in Microbiology, 2022)
Viral infection usually leads to cell death. Moderate cell death is a protective innate immune response. In contrast, excessive, uncontrolled cell death causes tissue destruction, cytokine storm, or even death of the host. In short, there is a contest between the host and the virus, the results of which determine the life or death of the host. Influenza A virus (IAV) infection in humans could lead to unbridled hyper-inflammatory reaction and cause serious illnesses and even death. A full understanding of the molecular mechanism and regulatory network of IAVs inducing cell death could help develop more effective antiviral treatment. In this review, we elaborate upon the current progress in research on cell death induced by IAV infection and dialectically understand the role of cell death in reducing IAV replication and disease prognosis.